PERENCANAAN PERKUATAN LERENG MENGGUNAKAN SHEET PILE SEBAGAI ALTERNATIF DINDING PENAHAN TANAH LERENG JEMBATAN KACA KAB.PROBOLINGGO - Dwi Septy Wahyuningdiah; Laily Endah Fatmawati; Yerry Kahaditu Firmansyah (Racic : Rab Construction Research, 2023)
Slopes are the plains of the earth that create an angle of inclination on the horizontal side. Slopes are formed in two ways, naturally (geological processes) or man-made. Several ways that can be used to avoid the formation of collapse are retaining walls by identifying the effect of the safety factor on slope stability under existing conditions. In this study it was intended to plan slope reinforcement using sheet piles with the help of the plaxis program and using the manual calculation of the fellenius method to determine the safety factor for slope stability to overcome landslide disasters on glass bridges. The results of this study are the results of the analysis of the factor of safety from manual fellenius calculations and using the help of the Plaxis software before being given reinforcement and after being given sheet pile reinforcement.